General rules for preparing blood for laboratory testing (Eurasian Journal of Learning and Academic Teaching, 2023)
Obtaining material for analysis Blood is taken from a vein Blood is taken from the finger Blood sampling from the wrist vein should be done with blood flow using a wide slotted cannula. The most common mistake in blood collection is the incorrect use of anticoagulant.